Evaluation of the multiple doses thiozonide's pharmacokinetics in patients diagnosed with pulmonary tuberculosis with multidrug-resistant or extensively drug-resistant Mycobacterium tuberculosis - А. Yu. Savchenko; V. G. Kukes; M. S. Burenkov; G. V. Ramenskaya (LLC "Publisher OKI", 2024)
Relevance. The increase in the number of cases of multidrug-resistant tuberculosis (MDR-TB) determines the relevance of the development of new anti-TB drugs (ATDs). Determining the pharmacokinetics of a drug in the context of MDR-TB therapy is an integral part of the study of the original drug. Objective. Evaluation of the pharmacokinetic properties of a new original drug, thiozonide, in patients with MDR-TB with multiple doses of the drug. Methods. Thiozonide was used in patients with a verified diagnosis of MDR-TB as part of a clinical trial according to protocol No. THIO22 "Multicenter 12-week doubleblind, randomized, placebo-controlled clinical trial on the selection of optimal dosages of the drug thiozonide, capsules (CJSC Pharm-Sintez") for against the background of standard anti-tuberculosis chemotherapy in patients diagnosed with pulmonary tuberculosis with multidrug-resistant or extensively drugresistant Mycobacterium tuberculosis" (permission of the Ministry of Health of the Russian Federation No. 661 dated 11/24/2014). Results. The pharmacokinetic characteristics of thiozonide were determined during its repeated use in patients diagnosed with pulmonary tuberculosis with multidrug-resistant or extensively drug-resistant mycobacterium tuberculosis, receiving standard anti-tuberculosis chemotherapy, by HPLC with mass spectrometric detection. The time to reach the maximum concentration T max of thiozonide with repeated administration at a dose of 200 mg, 400 mg and 600 mg was 4.21 ± 1.23 hours, 4.9 ± 1.08 and 5.29 ± 0.91, respectively; the half-life T1/2 for the same dosages of the drug was 7.84 ± 1.86, 7.56 ± 1.92 and 6.3 ± 2.12 hours, respectively. The maximum concentration of thiozonide after taking the drug thiozoinide by volunteers was Cmax was observed at the level of 1386.89 ± 533.68 ng / ml in the group taking 200 mg of thiozonide per day, 2684.48 ± 712.40 when taking the drug at a dosage of 400 mg and 5558, 99 ± 2143.81 - at a dosage of 600 mg. Conclusion. A linear dependence of the maximum concentration and the area under the pharmacokinetic curve on the dose taken and also the average concentration of thiozonide in the blood plasma of patients with pulmonary tuberculosis with multidrug resistance of the causative agent of the disease was revealed.